Elderly users of fall-risk-increasing drug perceptions of fall risk and the relation to their drug use - a qualitative study - Hege Therese Bell; Aslak Steinsbekk; Anne Gerd Granas (Taylor & Francis Group, 2017)
Objective: The aim of the study was to explore how home-dwelling elderly who use fall-risk-increasing drugs (FRIDs) perceive their fall risk and how they relate this to their drug use. Design, setting and subjects: A qualitative study with 14 home-dwelling elderly FRID users between 65 and 97 years in Central Norway participating in semi-structured individual interviews. The data were analyzed thematically by using systematic text condensation. Results: The main finding was that the informants did not necessarily perceive the use of FRIDs to be a prominent risk factor for falls. Some informants said they did not reflect upon drug use whatsoever and said they fully trusted their physician's choices. When either experiencing dizziness, fall episodes or by reading the patient information leaflet the informants said to either adjust their drug use or to contact their physician. Some felt rejected due to not getting their point across or their wish to alter the drug was not granted by the physician. Conclusions: Elderly FRID users did not necessarily relate their drug use to fall risk or struggled to present their perceived drug-related problems. Physicians need to regularly inform, monitor and assess the drug treatment when treating elderly with FRIDs.